-(4x-5)-(4x-6)+8=-7(x-1)-(5x+7)+3

Simple and best practice solution for -(4x-5)-(4x-6)+8=-7(x-1)-(5x+7)+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(4x-5)-(4x-6)+8=-7(x-1)-(5x+7)+3 equation:


Simplifying
-1(4x + -5) + -1(4x + -6) + 8 = -7(x + -1) + -1(5x + 7) + 3

Reorder the terms:
-1(-5 + 4x) + -1(4x + -6) + 8 = -7(x + -1) + -1(5x + 7) + 3
(-5 * -1 + 4x * -1) + -1(4x + -6) + 8 = -7(x + -1) + -1(5x + 7) + 3
(5 + -4x) + -1(4x + -6) + 8 = -7(x + -1) + -1(5x + 7) + 3

Reorder the terms:
5 + -4x + -1(-6 + 4x) + 8 = -7(x + -1) + -1(5x + 7) + 3
5 + -4x + (-6 * -1 + 4x * -1) + 8 = -7(x + -1) + -1(5x + 7) + 3
5 + -4x + (6 + -4x) + 8 = -7(x + -1) + -1(5x + 7) + 3

Reorder the terms:
5 + 6 + 8 + -4x + -4x = -7(x + -1) + -1(5x + 7) + 3

Combine like terms: 5 + 6 = 11
11 + 8 + -4x + -4x = -7(x + -1) + -1(5x + 7) + 3

Combine like terms: 11 + 8 = 19
19 + -4x + -4x = -7(x + -1) + -1(5x + 7) + 3

Combine like terms: -4x + -4x = -8x
19 + -8x = -7(x + -1) + -1(5x + 7) + 3

Reorder the terms:
19 + -8x = -7(-1 + x) + -1(5x + 7) + 3
19 + -8x = (-1 * -7 + x * -7) + -1(5x + 7) + 3
19 + -8x = (7 + -7x) + -1(5x + 7) + 3

Reorder the terms:
19 + -8x = 7 + -7x + -1(7 + 5x) + 3
19 + -8x = 7 + -7x + (7 * -1 + 5x * -1) + 3
19 + -8x = 7 + -7x + (-7 + -5x) + 3

Reorder the terms:
19 + -8x = 7 + -7 + 3 + -7x + -5x

Combine like terms: 7 + -7 = 0
19 + -8x = 0 + 3 + -7x + -5x
19 + -8x = 3 + -7x + -5x

Combine like terms: -7x + -5x = -12x
19 + -8x = 3 + -12x

Solving
19 + -8x = 3 + -12x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '12x' to each side of the equation.
19 + -8x + 12x = 3 + -12x + 12x

Combine like terms: -8x + 12x = 4x
19 + 4x = 3 + -12x + 12x

Combine like terms: -12x + 12x = 0
19 + 4x = 3 + 0
19 + 4x = 3

Add '-19' to each side of the equation.
19 + -19 + 4x = 3 + -19

Combine like terms: 19 + -19 = 0
0 + 4x = 3 + -19
4x = 3 + -19

Combine like terms: 3 + -19 = -16
4x = -16

Divide each side by '4'.
x = -4

Simplifying
x = -4

See similar equations:

| 4x-10+6x-40=180 | | x-2=15+8-9x | | 5x+2=2(2x+3) | | 1.5x-2=2(-x+1) | | -5x=11+4x | | graphy=x^2-x | | 4x-9-7x=-7x-11+3x | | u^2-9= | | 7x-9x+2=x-6+8 | | x-2=15x+8 | | 49w^2+56w+16= | | 3y^2+32y+20= | | 4z+9-2z=33-2z | | 4(x-7)=3(2x-1)+3 | | 5x-44=-8 | | 21x^2+19x-2= | | 22+9x=-12+8x | | 6u^2+48u+72= | | 7p+-3p=-4p+16 | | x=6-25 | | 15-4x=9-5x | | -10x=190 | | 7+2x=x+8 | | 8(-3v-7)=20-5v | | x=1/2(0+28.5)7 | | 1(4x+2)=4x-12(x-1) | | 4x+2=4+3x | | 1.2(5x-4)=3.6x-12(x+1) | | 7=1/2(0+28.5)x | | 2u^2+2u-60= | | -8+x=-2x-1 | | 10-5(6-2x)=6-(16-20x) |

Equations solver categories